Health, medicine, and society : key theories, future agendas - Williams, Simon J. (Simon Johnson), 1961-; Gabe, Jonathan; Calnan, Michael (Routledge, 2000)
Taking as its point of departure recent developments in health and social theory Health, Medicine and Society brings together a range of eminent, international scholars to reflect upon key issues at the turn of the century. Contributors draw upon a range of contemporary theories, both modernist and postmodernist, to look at the following themes: *health and social structure*the contested nature of the body*the salience of consumption and risk*the challenge of emotions Health, Medicine and Society provides a 'state-of-the-art' assessment of health related issues at the millennium and a cogent set of arguments for the centrality of health to contemporary social theory. Written in a clear, accessible style it will be ideal reading for students and researchers in health studies, public health, medical sociology, medicine and nursing.